Tadpole-Shaped POSS-Based Copolymers and the Aggregation Behavior at Air/Water Interface - Lin Zhu; Fang Chen; Xiaoyan Ma; Xiu Qiang; Zhiguang Li; Chen Dong; Duyang Zang (Advances in Condensed Matter Physics)
The aggregation behavior of three tadpole-shaped Polyhedral oligomeric silsesquioxane (POSS) based block copolymers using different blocks poly(methyl methacrylate) (PMMA) and poly(trifluoroethyl methacrylate) (PTFEMA) with different block sequence and ratio (POSS-PTFEMA161-b-PMMA236, POSS-PMMA277-b-PTFEMA130, and POSS-PMMA466-b-PTFEMA172) was investigated on the air-water interface. The interfacial rheology of three block copolymers was studied by surface pressure isotherm, compression modulus measurements, and compression and expansion hysteresis analysis on the Langmuir trough. The block sequence and ratio play a great role in self-assembly behavior at the interface. Based on surface pressure isotherm analysis, a thin film with low elasticity was achieved for the POSS-PTFEMA161-b-PMMA236. Moreover, for the block copolymer with same segment sequence (POSS-PMMA2-b-PTFEMA), the thin film compression capability is increased with increasing the PMMA ratio. The morphology of the deposited LB thin film was illustrated by atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS). We observed that a thin film was composed by crater-shaped quasi-2D micelles for POSS-PTFEMA-b-PMMA, while it was proved that only flaky texture was observed for both POSS-PMMA277-b-PTFEMA130 and POSS-PMMA466-b-PTFEMA172. The thickness and area of flaky aggregates were greatly related to PMMA ratio. The different interface self-assembly structure evolution was proposed based on the interfacial rheology and thin film morphology studies.